Search for a new Z′ gauge boson in 4μ events with the ATLAS experiment - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Castillo, Florencia Luciana; Rio, Fernando del; Czurylo, Marta; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Klassen, Martin; Mkrtchyan, Tigran; Ott, Philipp; et al. (Journal of high energy physics, 2023)
This paper presents a search for a new Z′ vector gauge boson with the ATLAS experiment at the Large Hadron Collider using pp collision data collected at $$ \sqrt{s} $$= 13 TeV, corresponding to an integrated luminosity of 139 fb−1. The new gauge boson Z′ is predicted by Lμ − Lτ models to address observed phenomena that can not be explained by the Standard Model. The search examines the four-muon (4μ) final state, using a deep learning neural network classifier to separate the Z′ signal from the Standard Model background events. The di-muon invariant masses in the 4μ events are used to extract the Z′ resonance signature. No significant excess of events is observed over the predicted background. Upper limits at a 95% confidence level on the Z′ production cross-section times the decay branching fraction of pp → Z′μμ → 4μ are set from 0.31 to 4.3 fb for the Z′ mass ranging from 5 to 81 GeV. The corresponding common coupling strengths, gZ′, of the Z′ boson to the second and third generation leptons above 0.003 - 0.2 have been excluded.
Veröffentlicht: 12. Juli 2023
*The ATLAS collaboration: G. Aad, L.M. Baltes, F. Bartels, F.L. Castillo, M.M. Czurylo, F. Del Rio, S.J. Dittmeier, M. Dunford, S. Franchino, M. Klassen, T. Mkrtchyan, P.S. Ott, D.F. Rassloff, S. Rodriguez Bosca, C. Sauer, A. Schoening, H.-C. Schultz-Coulon, V. Sothilingam, R. Stamen, P. Starovoitov, S.M. Weber, M. Wessels, L. Vigani, J. Zinsser [und sehr viele weitere Personen]
Gesehen am 14.12.2023